2004
DOI: 10.1159/000076242
|View full text |Cite
|
Sign up to set email alerts
|

Bigger Brains or Bigger Nuclei? Regulating the Size of Auditory Structures in Birds

Abstract: Increases in the size of the neuronal structures that mediate specific behaviors are believed to be related to enhanced computational performance. It is not clear, however, what developmental and evolutionary mechanisms mediate these changes, nor whether an increase in the size of a given neuronal population is a general mechanism to achieve enhanced computational ability. We addressed the issue of size by analyzing the variation in the relative number of cells of auditory structures in auditory specialists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 51 publications
1
47
1
Order By: Relevance
“…There are several interesting differences between the chicken and the owl NL, not least the different anatomical orientation of the ITD maps. However, this is convincingly explained by the hyperplasia of the owl's NL and its specialisations for highfrequency processing (reviews in Grothe et al 2004;Kubke et al 2004). A recent in vitro study on the emu's NL showed physiological delay lines along the same anatomical axis and in the same direction as in the chicken (MacLeod et al 2006), supporting the hypothesis that this is the plesiomorphic pattern in birds.…”
Section: Maps Of Itd and Axonal Delay Linesmentioning
confidence: 91%
“…There are several interesting differences between the chicken and the owl NL, not least the different anatomical orientation of the ITD maps. However, this is convincingly explained by the hyperplasia of the owl's NL and its specialisations for highfrequency processing (reviews in Grothe et al 2004;Kubke et al 2004). A recent in vitro study on the emu's NL showed physiological delay lines along the same anatomical axis and in the same direction as in the chicken (MacLeod et al 2006), supporting the hypothesis that this is the plesiomorphic pattern in birds.…”
Section: Maps Of Itd and Axonal Delay Linesmentioning
confidence: 91%
“…For example, comparisons of relative forebrain size have suggested a similar overall neural architecture in corvids and parrots [Psittaciformes; Emery and Clayton, 2004]. Volumetric studies also indicate the convergent neural evolution of telencephalic composition in some aquatic species [Carezzano and Bee de Speroni, 1995], medullary nuclei in auditory specialists [Kubke et al, 2004] and overall brain composition in parrots and passerines [Iwaniuk et al, 2005]. In a recent analysis of major brain components, Burish et al [2004] also provide some evidence for cerebrotypes in birds.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation is called the 'principle of proper mass' whereby the size of a neural structure is a reflection of the complexity of the behaviors that it subserves [Jerison, 1973]. Examples of this correlation are found in all sensory systems and in all vertebrates [e.g., somatosensory: Pubols et al, 1965;Pubols and Pubols, 1972;visual: Barton, 1998;Iwaniuk and Wylie, 2007;gustatory: Finger, 1975; auditory: Kubke et al, 2004]. Some of the best-studied examples of this correlation between sensory systems and behavior come from examinations of the trigeminal system in small mammals and its representation in the primary somatosensory cortex .…”
Section: Introductionmentioning
confidence: 99%